Brain imaging in behavioral medicine and clinical neuroscience - Cohen, Ronald A.; Sweet, Lawrence H.; SpringerLink (Online service). (New York Springer, 2011)
Rapid developments in brain neuroimaging methods have occurred over the past decade. This is the first book to address the application of brain imaging to behavioral medicine, despite the large number of research projects initiated over recent years.
Electronic reproduction.
Keywords: Brain -- Imaging; Brain -- Diseases -- Imaging; Brain -- Radiography; Behavioral medicine -- Methods; Diagnostic imaging -- Methods; Neuroradiography -- Methods; Neurosciences -- Methods